How genome editing could help cure XLRP.
Thanks to funding under the REGAIN project, Dr Knut Stieger, Professor of Experimental Ophthalmology at the University of Giessen, is well on track to finding a treatment for X-linked retinitis pigmentosa (XLRP). His research is set not only to benefit XLRP patients, but also to advance the state-of-the-art in targeted genre correction strategies.